2015
DOI: 10.1136/annrheumdis-2015-eular.3653
|View full text |Cite
|
Sign up to set email alerts
|

AB0573 Neutrophil-Lymphocyte Ratio is not Superior to Lymphocyte Count Alone in Differentiating Disease Activity in SLE

Abstract: BackgroundNeutrophil-lymphocyte ratio (NLR) integrates the deleterious effects of neutrophilia and lymphopenia, and has been used as diagnostic and prognostic biomarker in various diseases (1). NLR was recently proposed as an inflammatory biomarker in systemic lupus erythematosus (SLE) (2).Objectives1. To compare the neutrophil count (NEU), lymphocyte count (LYM) and NLR between lupus patients with active disease and those with inactive disease. 2. To determine the diagnostic accuracy of these markers for dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…In general, our findings are consistent with those reported in this meta-analysis. However, in a subsequent study, we found no evidence of association between neutrophil to lymphocyte ratio and Mex-SLEDAI [6].…”
Section: Identification Of Eligible Studiescontrasting
confidence: 65%
See 1 more Smart Citation
“…In general, our findings are consistent with those reported in this meta-analysis. However, in a subsequent study, we found no evidence of association between neutrophil to lymphocyte ratio and Mex-SLEDAI [6].…”
Section: Identification Of Eligible Studiescontrasting
confidence: 65%
“…In February 2015, we reported our findings on this topic at the XLIII Mexican Congress of Rheumatology, which later appeared as abstracts in a supplement of Reumatología Clínica [3][4][5], the official publication of the Spanish Society of Rheumatology and the Mexican College of Rheumatology. We included 36 adult lupus patients with inactive disease (Mexican version of the Systemic Lupus Erythematosus Disease Activity Index [Mex-SLEDAI]) and 56 healthy controls.…”
Section: Identification Of Eligible Studiesmentioning
confidence: 99%
“…Neutrophil-to-lymphocyte ratio (NLR) represents a combination of two of these markers, and is superior to other WBC-derived parameters, due to its stability ( 3 , 4 ). NLR has been studied in many autoimmune disorders such as systemic lupus erythematosus (SLE) ( 5 ), Sjögren syndrome (SS) ( 6 ), Behçet disease ( 7 ), Hashimoto disease ( 8 ), multiple sclerosis (MS) ( 9 12 ), among others. Co-existing autoimmune disorders, including both SLE and SS, are not uncommon in AQP4-ab-positive NMOSD ( 13 ).…”
Section: Introductionmentioning
confidence: 99%